Public sector governance and service delivery in Nigeria: Issues and challenges - Mark, Ochala; Zainuddin, Ruslan (School of Social Sciences, USM, 2017)
This paper explore the propensity of the Nigerian public service to adequately manage public affairs. The paper focus on the significance of public service delivery to the citizens in a manner that will enhance or improve service delivery to the generality of the masses, in a civilian administration in Nigeria. The paper uncovered that government reform introduced to improve service delivery have not been yielding any positive result. Why this persistence failure is as a result of reform of public service delivery called SERVICOM to achieve its objectives. This is can be traceable to lack of political will on the part of government and the governed. Therefore, limiting its operations. The paper advocate that SERVICOM should gained a wide publicity, proper coordination, given it a “legal backing” to make it efficient and effective.